Great Lakes Accelerated Innovation Delivery Initiative Rapid Delivery Hub in Burundi - Part1 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
AIDI Great Lakes Region (AID-I GLR) is disseminating agronomic technologies in Burundi to improve the livelihood of smallholder farmers. In this video, a farmer in Kirundo Province shares positive feedback from the field-level experience after implementing agronomic practices recommended under AIDI framework.